Quality estimation of stochastic control system using simulation methods - Aidokas, Linas; Telksnys, Laimutis Adolfas (Lietuvos matematikos rinkinys, 2021)
The stochastic control system is investigated. The article solves the problem of human-robot humanoid communication. The problem arises in the development of human behavior formation management systems. They describe human behavior in terms of probabilistic characteristics. Such control systems are stochastic. The management system of human behavior formation and its functioning is described quality assessment. The problem is solved by simulation modeling. The software implementing the method is described. The results of experimental research are presented.